Ancestral genomic duplication of the insulin gene in tilapia: An analysis of possible implications for clinical islet xenotransplantation using donor islets from transgenic tilapia expressing a humanized insulin gene. Issue 4 (3rd July 2016) - Hrytsenko, Olga; Pohajdak, Bill; Wright, James R.
ABSTRACT: Tilapia, a teleost fish, have multiple large anatomically discrete islets which are easy to harvest, and when transplanted into diabetic murine recipients, provide normoglycemia and mammalian-like glucose tolerance profiles. Tilapia insulin differs structurally from human insulin which could preclude their use as islet donors for xenotransplantation. Therefore, we produced transgenic tilapia with islets expressing a humanized insulin gene. It is now known that fish genomes may possess an ancestral duplication and so tilapia may have a second insulin gene. Therefore, we cloned, sequenced, and characterized the tilapia insulin 2 transcript and found that its expression is negligible in islets, is not islet-specific, and would not likely need to be silenced in our transgenic fish.